Evaluations of in-use emission factors from off-road construction equipment. (December 2016) - Cao, Tanfeng; Durbin, Thomas D.; Russell, Robert L.; Cocker, David R.; Scora, George; Maldonado, Hector; Johnson, Kent C.
Abstract: Gaseous and particle emissions from construction engines contribute an important fraction of the total air pollutants released into the atmosphere and are gaining increasing regulatory attention. Robust quantification of nitrogen oxides (NOx ) and particulate matter (PM) emissions are necessary to inventory the contribution of construction equipment to atmospheric loadings. Theses emission inventories require emissions factors from construction equipment as a function of equipment type and modes of operation. While the development of portable emissions measurement systems (PEMS) has led to increased studies of construction equipment emissions, emissions data are still much more limited than for on-road vehicles. The goal of this research program was to obtain accurate in-use emissions data from a test fleet of newer construction equipment (model year 2002 or later) using a Code of Federal Requirements (CFR) compliant PEMS system. In-use emission measurements were made from twenty-seven pieces of construction equipment, which included four backhoes, six wheel loaders, four excavators, two scrapers (one with two engines), six bulldozers, and four graders. The engines ranged in model year from 2003 to 2012, in rated horsepower (hp) from 92 to 540 hp, and in hours of operation from 24 to 17, 149 h. This is the largest study of off-road equipment emissions using 40 CFR part 1065 compliant PEMS equipment for all regulated gaseous and particulate emissions. Highlights: In-use emission measurements were made from twenty-seven pieces of construction equipment, which included four backhoes, six wheel loaders, four excavators, two scrapers (one with two engines), six bulldozers, and four graders. This is the largest study of off-road equipment emissions using 40 CFR part 1065 compliant PEMS equipment for all regulated gaseous and particulate emissions. The large variability in emissions, especially for NOx and PM, could have important implications for developing accurate emissions inventories and models. This variability is primarily due to differences in engine load factors for different types of work and combinations of work and idle time and the displacement of the engines.